2020
DOI: 10.1186/s13293-020-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific association between the gut microbiome and high-fat diet-induced metabolic disorders in mice

Abstract: Background Accumulating evidence indicates that high-fat diet (HFD)-induced metabolic disorders are associated with dysbiosis of the gut microbiota. However, the sex-specific characteristics of the gut microbiota and its association with a sexually dimorphic response to a HFD remain unclear. Methods Male and female mice were randomly assigned to receive a chow diet (CD) or HFD for 12 weeks. A group of HFD mice were pretreated with antibiotic cocktails for 4 weeks. Body weight, insulin sensitivity and the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 37 publications
(44 reference statements)
4
49
0
Order By: Relevance
“…5,6 Sex-related differences have been reported in the composition of gut microbiota for both rodents and humans. [7][8][9][10][11][12][13][14][15][16] Decrease in αdiversity of microbiota in the gut is associated with obesity, 17,18 and α-diversity is lower on average in males compared to females, [10][11][12]14 especially in young adults (ages 20 to 45 years) compared to middle-aged adults. 10 The effect of sex on gut microbiota composition is larger than that observed in response to a high-fat diet (HFD) or treatment with antibiotics, 8 but is smaller than effects due to genotype.…”
Section: Role Of Androgens In Sexual Maturation and Sex-related Diffementioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Sex-related differences have been reported in the composition of gut microbiota for both rodents and humans. [7][8][9][10][11][12][13][14][15][16] Decrease in αdiversity of microbiota in the gut is associated with obesity, 17,18 and α-diversity is lower on average in males compared to females, [10][11][12]14 especially in young adults (ages 20 to 45 years) compared to middle-aged adults. 10 The effect of sex on gut microbiota composition is larger than that observed in response to a high-fat diet (HFD) or treatment with antibiotics, 8 but is smaller than effects due to genotype.…”
Section: Role Of Androgens In Sexual Maturation and Sex-related Diffementioning
confidence: 99%
“… 14 , 15 Sex differences in gut microbiota are also suggested to play a role in the development of other diseases that show a sex bias, including rheumatoid arthritis, 19 anxiety disorder, 20 hepatocellular carcinoma, 21 and inflammatory bowel disease. 11 , 22 Sex-by-diet interactions in gut microbiota have been observed in C57BL/6 J mice 7 , 8 and humans, 9 and gut microbiota play a critical role in HFD-induced obesity and insulin resistance. 23 The combinatorial effects of androgen and diet may therefore induce pathological conditions that have a sex bias through modulation of gut microbiota.…”
Section: Role Of Androgens In Sexual Maturation and Sex-related Diffementioning
confidence: 99%
“…Holdemanella spp. has been reported to be positively associated with chronic kidney disease [65] and the android fat ratio in male [66], and Turicibacter spp. were positively associated with inflammation [67].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have highlighted a reduction in OA histopathologic severity in female mice, in both young and old animals [43,44]. Although not evaluated directly in the context of OA, sex-specific differences in the gut microbiome have been described in association with known OA risk factors, including high fat diet-induced obesity [45,46] and advanced age [47]. In the present study, our 16S analysis identified 18 sex-associated microbiome clades; among these, 7 overlapped with our MRL vs. B6 comparison.…”
Section: Discussionmentioning
confidence: 99%